2008
DOI: 10.1111/j.1442-9071.2008.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Butterflies and black lacy patterns: the prevalence and characteristics of Charles Bonnet hallucinations in an Australian population

Abstract: The prevalence of CBS in the older-aged, low-vision population is 17.5%. Several demographic and syndrome-specific characteristics were found to be consistent enabling a profile of a CBS sufferer in this group of participants to be compiled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 33 publications
4
79
1
12
Order By: Relevance
“…This prevalence rate is lower compared to some previously reported rates (Khan et al 2008), but close to the prevalence of 13% described in 100 consecutive patients with AMD (Holroyd et al 1992) and 11% described in 300 low-vision patients (Teunisse et al 1995). An Australian study of 200 patients with variable retinal disease and a visual acuity of 0.5 or less found a prevalence rate of 17.5% (Vukicevic & Fitzmaurice 2008), while another report of 66 patients with AMD and a visual acuity of logMAR 0.6 or less found that 15% of the patients reported symptoms of CBS (Abbott et al 2007). If we exclude all patients with a visual acuity of more than 0.5 on the best seeing eye from our material, we get a prevalence rate of 12%, which increases to 15% if we only include patients with a visual acuity of 0.3 or less on the best seeing eye.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This prevalence rate is lower compared to some previously reported rates (Khan et al 2008), but close to the prevalence of 13% described in 100 consecutive patients with AMD (Holroyd et al 1992) and 11% described in 300 low-vision patients (Teunisse et al 1995). An Australian study of 200 patients with variable retinal disease and a visual acuity of 0.5 or less found a prevalence rate of 17.5% (Vukicevic & Fitzmaurice 2008), while another report of 66 patients with AMD and a visual acuity of logMAR 0.6 or less found that 15% of the patients reported symptoms of CBS (Abbott et al 2007). If we exclude all patients with a visual acuity of more than 0.5 on the best seeing eye from our material, we get a prevalence rate of 12%, which increases to 15% if we only include patients with a visual acuity of 0.3 or less on the best seeing eye.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, differences in cultural or ethnic groups and type of disease may also play a role in the variation. In fact, only about 1 ⁄ 5 of the patients admit to have told others about their symptoms (Vukicevic & Fitzmaurice 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Santhouse et al reported that the hallucinations were an emotional burden in 50% of 34 patients, and half of them were egodystonic [22]. Similarly, Vukicevic and Fitzmaurice reported that the syndrome caused moderate or severe stress in 16 of 35 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic and psychiatric problems should first be excluded before diagnosing the problem as CBS [7]. No official mode of treatment has been described [6]. However, a recent study showed the effectiveness of selective serotonin reuptake inhibitors [13].…”
Section: At Least One Complex Visual Hallucination Within the Past 4 mentioning
confidence: 99%
“…It causes these people to see things that aren't really there, known as visual hallucinations. These people are psychologically normal and have no preexisting psychiatric illness that manifests hallucinations [3][4][5][6]. About 12% to 13% of patients with impaired sight have visual hallucinations [7].…”
Section: "People Call Me Blind Yet I Can See Things That Others Don'mentioning
confidence: 99%